The Relationship Between Peer Social Support and Anxiety in Facing Nursing Student Skill Laboratory Examinations - Syafni Gusti Windari; Ari Rahmat Aziz; Ganis Indriati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Anxiety is a problem that is often found in nursing students. One of the reasons is because students are required to pass laboratory skill exams, which creates pressure and causes anxiety. Peer social support is one of the factors that can influence anxiety. The aim of the study was to determine the relationship between peer social support and anxiety in facing laboratory skill exams in nursing students. The research design is a descriptive correlation with a cross sectional approach. The respondents of this study were 244 students of the Faculty of Nursing, University of Riau, who were obtained using the proportionate stratified random sampling technique. The measuring tool is a questionnaire and the data analysis used is the Kolmogorov-Smirnov test. The results showed that there was a relationship between peer social support and anxiety in facing laboratory skill exams in nursing students with p value = 0.000 Î± (0.05). Anxiety that occurs in nursing students in facing laboratory skill exams has a correlation with social support, one of which is the social support of peers.